Day‐to‐day sleep variability with Alzheimer's biomarkers in at‐risk elderly - Andrée‐Ann Baril; Cynthia Picard; Anne Labonté; Erlan Sanchez; Catherine Duclos; Béry Mohammediyan; Nicholas J. Ashton; Henrik Zetterberg; Kaj Blennow; John C. S. Breitner; Sylvia Villeneuve; Judes Poirier; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2024)
Abstract INTRODUCTION Measuring day‐to‐day sleep variability might reveal unstable sleep‐wake cycles reflecting neurodegenerative processes. We evaluated the association between Alzheimer's disease (AD) fluid biomarkers with day‐to‐day sleep variability. METHODS In the PREVENT‐AD cohort, 203 dementia‐free participants (age: 68.3 ± 5.4; 78 males) with a parental history of sporadic AD were tested with actigraphy and fluid biomarkers. Day‐to‐day variability (standard deviations over a week) was assessed for sleep midpoint, duration, efficiency, and nighttime activity count. RESULTS Lower cerebrospinal fluid (CSF) ApoE, higher CSF p‐tau181/amyloid‐β (Aβ)42, and higher plasma p‐tau231/Aβ42 were associated with higher variability of sleep midpoint, sleep duration, and/or activity count. The associations between fluid biomarkers with greater sleep duration variability were especially observed in those that carried the APOE4 allele, mild cognitive impairment converters, or those with gray matter atrophy. DISCUSSION Day‐to‐day sleep variability were associated with biomarkers of AD in at‐risk individuals, suggesting that unstable sleep promotes neurodegeneration or, conversely, that AD neuropathology disrupts sleep‐wake cycles.